Application of 2D MXene in Organic Electrode Materials for Rechargeable Batteries: Recent Progress and Perspectives. (29th January 2023) - Wang, Zhengran; Jiang, Huiyu; Zhang, Yuchan; An, Yongling; Wei, Chuanliang; Tan, Liwen; Xiong, Shenglin; Qian, Yitai; Feng, Jinkui
Abstract: Organic electrode materials (OEMs) are emerging green power because of the promising advantages such as environmental friendliness, abundant sources, easy recycling, and structural diversity. However, several inherent issues, including low electronic conductivity, dissolution of active materials, and particle pulverization restrict their practical application. MXene, as a novel 2D material has exhibited enormous potential to solve the issues of OEMs due to its high conductivity, unique structure, exceptional mechanical property, and abundant surface groups. Up to now, various effective strategies have been presented and achieved positive effects, such as constructing heterojunction structures, in situ assembly, dip‐coating, preparing free‐standing MXene paper, etc. Nonetheless, comprehensive review of the progress and status is rare. Herein, an overview of the application of MXene in organic electrode materials for rechargeable batteries is systematically put forward. Meanwhile, recent progress and future development directions are presented. This review can serve as a guide for future research. Abstract : The recent progress with regard to the application of MXene in organic electrode materials is systematically reviewed. 2D MXene with excellent characteristics can effectively solve the issues of OEMs such as low electronic conductivity, dissolution and particle pulverization. Many effective strategies are comprehensively summarized, including construction of heterojunction structures, in situ assembly, dip‐coating, and fabrication of free‐standing MXene paper, etc.